Petroleum Exploration and Production Rights : Allocation Strategies and Design Issues - Tordo, Silvana; Johnston, David; Johnston, Daniel (World Bank, 2012)
Petroleum has become an integral part of today's global economy and a key component of many national economies. Hence, the presence of petroleum in meaningful quantities can have important economic, developmental, and strategic consequences for a country. While a country's petroleum resource base is a gift of nature, translating this resource into saleable crude oil requires investment and effort. Whether governments choose to invest directly or allow private investors to do so, their primary concern should be to maximize the social benefits derived from the exploitation of the resource base. In practice, however, defining what constitutes maximum social welfare is essentially a political question, which helps explain the variety of objectives pursued by governments over time. In order to exploit their natural resources efficiently, many governments rely on private oil companies. Governments have a challenging task in deciding which companies should be awarded the exclusive rights to explore, develop, and produce their resources, and on what conditions such rights should be awarded. There is little empirical documentation on the design and relative effectiveness of alternative systems for the allocation of petroleum exploration, development, and production (E&P) rights and their policy implications. This paper analyzes the available evidence on the advantages and disadvantages of various practices used by petroleum producing countries to allocate petroleum E&P rights, and draws conclusions about the optimal design of E&P allocation systems.